إشكالية صياغة المصطلح النّحوي في لغة التخصّص The Problem Of Formulating A Gramatical Term In The Language Of Speciality - نسرين, غجاتي; يوسف, وسطاني (جامعة الوادي - University of Eloued, 2021)
يهدف هذا المقال إلى الوقوف على أهم المشاكل المعيقة في وضع المصطلح العلمي عموما والمصطلح النحوي خاصة، والآليات العلمية في رصده والاتفاق عليه, فإذا كانت المصطلحات مفاتيح العلوم على حدّ تعبير الخوارزمي, فإن الولوج إلى أي علم من العلوم اللّغوية يتطلب وضع المصطلح بضوابط علمية, فكان لزاما أن نتحدث عن العلاقة بين المصطلح وعناصر لغة التخصّص، بناء على إبراز موقعية المصطلح من اللّغة الخاصة, مع مراعاة الإشكالية التي يقع فيها واضع المصطلح العلمي والنحوي خاصة, وأهم العوائق التي تصادفه, وبناء علية، أ يمكن للعلماء توحيد هذه الآليات؟ أم أن هذا هو الإشكال الواقع؟. In this article, we have shed light on the most important problems that hinder the development of the scientific term in general and the grammatical term in particular, and the scientific mechanisms in monitoring and agreement on it. If the terms are the keys to the sciences in the words of Al-Khwarizmi, then access to any linguistic world requires us putting the term in scientific regulations. So, it was required to talk about the interrelation between the term and all the components and the elements of the language of the specialization, and this is evidenced by highlighting the location of the term from the private language, taking into account the problem in which the author of the scientific and grammatical term in particular falls, and the most important obstacles encountered, and based on this, Can scientists unify these mechanisms? Or is this the real problem? This is what the article is trying to reach.
مقال
Keywords: المصطلح؛ الترجمة؛ التعريب؛ العلم؛ لغة التخصص; Term; Translation; Arabization; Science; Language of Specialization.